In Obese Patients With Type 2 Diabetes, Mast Cells in Omental Adipose Tissue Decrease the Surface Expression of CD45, CD117, CD203c, and FcϵRI - Lopez-Perez, David; Redruello-Romero, Anaïs; Garcia-Rubio, Jesús; Arana, Carlos; Garcia-Escudero, Luis A.; Tamayo, Francisco; Salmeron, Javier; Galvez, Julio; Leon, Josefa; Carazo, Ángel (Frontiers in Endocrinology, 2022)
The paradigm of mast cells in type 2 diabetes is changing. Although they were first considered deleterious inflammatory cells, now they seem to be important players driving adipose tissue homeostasis. Here we have employed a flow cytometry-based approach for measuring the surface expression of 4 proteins (CD45, CD117, CD203c, and FcεRI) on mast cells of omental (o-WAT) and subcutaneous white adipose tissue (s-WAT) in a cohort of 96 patients with morbid obesity. The cohort was split into three groups: non-T2D, pre-T2D, and T2D. Noteworthy, patients with T2D have a mild condition (HbA1c <7%). In o-WAT, mast cells of patients with T2D have a decrease in the surface expression of CD45 (p=0.0013), CD117 (p=0.0066), CD203c (p=0.0025), and FcεRI (p=0.043). Besides, in s-WAT, the decrease was seen only in CD117 (p=0.046). These results indicate that T2D affects more to mast cells in o-WAT than in s-WAT. The decrease in these four proteins has serious effects on mast cell function. CD117 is critical for mast cell survival, while CD45 and FcεRI are important for mast cell activation. Additionally, CD203c is only present on the cell surface after granule release. Taking together these observations, we suggest that mast cells in o-WAT of patients with T2D have a decreased survival, activation capacity, and secretory function.